Interpretasi Humanistik Kebahasaan: Upaya Kontekstualisasi Kaidah Bahasa Arab - Abd Aziz; Saihu Saihu (Arabiyatuna : Jurnal Bahasa Arab, 2019)
This research concludes that language and humanity are inseparable needs, where language is a tool for thinking for humans. Language which is an expression of the meaning it contains and the ideas it captures come from the universality of universality, including humanity. This research uses descriptive analysis method, by concluding all the data presented in this study. Halliday as one of the basic arguments in writing this article also explained that the function of interactional language, where human interaction is intertwined, one of which is through language, in this context is Arabic. As language users, humans have the emotive and imaginative power to interpret what they hear, what they say, and what they see. When Arabic is released into the public sphere, the resulting meaning will have a contextual correlation, and this meaning also adjusts to the interpreter's conceptual reference. The meaning that is covered by the language rules is extracting humanistic values as a form of enthusiasm to contextualize language texts in a wider scope.